1986
DOI: 10.1111/j.1440-1681.1986.tb00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Changes in Blood Pressure, Aldosterone and Body Fluids During Enalapril Treatment: A Double‐blind Randomized Study vs Hydrochlorothiazide Plus Propranolol in Essential Hypertension

Abstract: Aldosterone suppression is said to play a major role in the long term hypotensive efficacy of angiotensin converting enzyme inhibitors. However, in previous reports from other laboratories, plasma volume has been found mostly increased and sodium balance sometimes positive. The effects of the angiotensin converting enzyme inhibitor enalapril (10-40 mg/day, p.o., for 6 weeks) on blood pressure, body fluid volumes, renal function and plasma aldosterone were compared to those of hydrochlorothiazide (50 mg/day, p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…ACE‐1 is present in abundance in human glomeruli, 6 allowing renin‐dependent variations in the rate of generation of Ang II, which, in turn, modulate renal vascular resistance, efferent arteriolar tone, and glomerular filtration pressure. ACE‐1 inhibitors reduce adrenal aldosterone release in response to acute stimuli such as posture or salt‐depletion 7 but have little effect on plasma aldosterone chronically 8 . A more comprehensive explanation of the BP‐lowering effects of ACE inhibitors is offered by extensive observations that the brain and the cerebral vasculature respond to both local and systemic RAS systems.…”
Section: The Rasmentioning
confidence: 99%
“…ACE‐1 is present in abundance in human glomeruli, 6 allowing renin‐dependent variations in the rate of generation of Ang II, which, in turn, modulate renal vascular resistance, efferent arteriolar tone, and glomerular filtration pressure. ACE‐1 inhibitors reduce adrenal aldosterone release in response to acute stimuli such as posture or salt‐depletion 7 but have little effect on plasma aldosterone chronically 8 . A more comprehensive explanation of the BP‐lowering effects of ACE inhibitors is offered by extensive observations that the brain and the cerebral vasculature respond to both local and systemic RAS systems.…”
Section: The Rasmentioning
confidence: 99%
“…[82][83][84] Enalapril has been shown to cause transient increases in interstitial fluid volume after 1 week of administration, but these increases are short-lived, and extracellular fluid volume returns to baseline after 6 weeks of therapy. 85 Other studies have demonstrated that changes in body weight, extracellular fluid, and plasma volume are minimal with ACEIs. 86,87 Most studies have reported a low prevalence of edema in subjects treated with an ACEI.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%